Architectural Aspects of Self-Aware and Self-Expressive Computing Systems: From Psychology to Engineering. - Lewis, Peter R.; Chandra, Arjun; Faniyi, Funmilade; Glette, Kyrre; Chen, Tao; Bahsoon, Rami; Torresen, Jim; Yao, Xin (Computer (00189162), 2015)
Work on human self-awareness is the basis for a framework to develop computational systems that can adaptively manage complex dynamic tradeoffs at runtime. An architectural case study in cloud computing illustrates the framework's potential benefits.